The how-tos of hiring. - Kariya, S. (IEEE spectrum)
The author describes how firms can be more selective in a downturn, but the basic rules of recruiting still apply. The upside of hiring in an economic slowdown is that there's a bigger pool of higher-quality applicants to choose from. In fact, some firms are viewing this as an opportunity to replace existing employees with new recruits